The Effectiveness of Guided Inquiry Learning Model to Improve Science Literacy Skills and Students Self Efficacy on AcidBase Materials - Haniska Virginia Pitaloka; Emmawaty Sofya; Tasviri Efkar (Universitas Lampung, 2020)
This research was aimed to gain an information about the effectiveness of guided inquiry learning model in improving students' science literacy and self efficacy on acid-base material. This research method is a quasi-experimental with pretest postest control group design. The population in this study were all students of class XI MIA SMA Negeri 3 Metro of the 2019/2020 school year. Sampling on this study are XI MIA 2 as the experimental class and XI MIA 3 as the control class. The effectiveness of guided inquiry learning model was analyzed using the two mean difference test at n-Gain and the effect size test on students' science literacy and self efficacy. The results showed that guided inquiry learning model had a